Xeno-free extraction, culture, and cryopreservation of human adipose-derived mesenchymal stem cells (2016)
Molecules of animal or bacterial origin, which pose a risk for zoonoses or immune rejection, are com-monly used for extraction, culture, and cryopreservation of mesenchymal stem cells. There is no se-quentialandorderlyprotocolforproducinghumanadipose-derivedstemcells(hASCs)underxeno-freeconditions. Afterstandardizinga humanplateletlysate (hPL) productionprotocol,four humanadiposetissue samples were processed through explants with fetal bovine serum (FBS)-supplemented or hPL-supplemented media for extracting the adipose-derived stem cells. The cells were cultivated in cellculture medium + hPL (5%) or FBS (10%). The cellular replication rate, immunophenotype, and differ-entiation potential were evaluated at fourth passage. Cellular viability was evaluated before and aftercryopreservation of the cells, with an hPL-based solution compared with an FBS-based solution. Theexplants cultured in hPL-supplemented media showed earlier and faster hASC proliferation than didthosesupplementedwithFBS.Likewise,cellsgrowninhPL-supplementedmediashowedagreaterpro-liferation rate, without losing the immunophenotype. Osteogenic differentiation of xeno-free hASCwas higher than the hASC produced in standard conditions. However, adipogenic differentiationwas reduced in xeno-free hASC. Finally, the cells cryopreserved in an hPL-based solution showed ahigher cellular viability thanthecells cryopreserved inanFBS-based.In conclusion, we have developeda complete xeno-free protocol for extracting, culturing, and cryopreserving hASCs that can be safelyimplemented in clinical studies.